Identification of Alexandrium Halim (Dinophyceae) using EPI-fluorescence microscopy - Po, T.L; Chui, P.L; Usup, G. (Annals of Microscopy, 2003)
Alexandriumspecies is a group of dinoflagellates comprise of more than 20 different toxic and non toxic species More than half of them are capable in producing a type of neurotoxins called saxitoxins which act as a sodium channel blocker in mammalian nerve system. The occurrences of toxic Alexandrium blooms have increased tremendously over the past decade throughout the world. Lack of distinctive characteristic such as horn, spine or heavy ornamentation of the thecal plates caused the difficulty in identification of this ...